Streamside Runoff: v.11:no.2(1999:summer/fall) - Center for Streamside Studies (University of Washington Water Center, 1999)
Articles include: Conifer Regeneration; River Regulation and Salmonid Growth; Lummi Nation Riparian Research.
Keywords: watersheds; watershed hydrology; watershed management; cooperative research; water; Pacific States; Washington; conifers; forest regeneration; natural regeneration; coniferous forests; rivers; Salmonidae; limnology; osmoregulation; riparian areas